PENGGUNAAN PERMAINAN TRADISIONAL EGRANG BATOK KELAPA DALAM MENINGKATKAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI PAUD AYUNI TEMBUNG - Pamela, Rika Sri; Daulay, Nurussakinah; Pulungan, Enny Nazrah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This research was carried out at PAUD Ayuni Tembung. Another problem in this research is what obstacles children face when playing the traditional game of coconut shell stilts in the gross motor development of children aged 5-6 years at PAUD Ayuni Tembung. The aim of this research is to determine the obstacles faced by children when playing the traditional game of coconut shell stilts in the gross motor development of children aged 5-6 years at PAUD Ayuni Tembung. The research method used is